Lower Goru Formation-3D Modeling and Petrophysical Interpretation of Sawan Gas Field, Lower Indus Basin, Pakistan - Abbas, S. T.; Mirza, K.; Arif, S. J. (The Nucleus, 2015)
Sawan Gas field is tectonically stable area as it is a part of Platform region and far away from collision zone. The present study deals with the interpretation of available seismic and well logs data to evaluate the subsurface structure to interpret the occurring of hydrocarbons in the study area of Lower Indus Basin. Seismic modeling (structural interpretations of seismic sections and 3D subsurface structure modeling) and petrophysical properties of reservoir were carried out in this work using the software SMT Kingdom Suite 8.3. Reflectors marked in all seismic sections are continuous with little folding there by indicating presence of subsurface stratigraphic-cumstructural traps. Petrophysical parameters point to presence of reservoir potentials at different depth in both wells due to low water saturation and good effective porosities.